Microbial Starch‐Converting Enzymes: Recent Insights and Perspectives - Miao, Ming; Jiang, Bo; Jin, Zhengyu; BeMiller, James N. (Comprehensive reviews in food science and food safety, 2018)
Starch is an abundant, natural, renewable resource, and present as the major storage carbohydrate in the seeds, roots, or tubers of many important food crops, such as maize, wheat, rice, potato, and cassava. Uses of native starches in most industrial applications are limited by their inherent properties. Hence, they are often structurally modified after isolation to enhance desirable attributes, to minimize undesirable attributes, or to create new attributes. Enzymatic, rather than chemical, approaches are used in the production of starch syrups, maltodextrins, and cyclodextrins. However, the desire for starch‐active enzymes working optimally at high temperatures and low pH conditions with superior stability and activity is still not satisfied and this stimulates interest in developing novel and improved starch‐active enzymes through a variety of strategies. This review provides current information on enzymes belonging to GH13, 57, 70, and 77 that can be used in structural modifications of the starch polysaccharides or to produce starch‐derived products from them. The characteristics and catalytic mechanisms of microbial enzymes are discussed (including 4‐α‐glucanotransferase, branching enzyme, maltogenic amylase, cyclomaltodextrinase, amylosucrase, and glucansucrase). Product diversity after starch‐converting reaction and utilization in industrial applications are also dealt with.